PARTICIPATORY VIDEO FOR DEVELOPING SPIRIT OF INNOVATION IN SOCIO-ECONOMICALLY UNDERPRIVILEGED HIGH SCHOOL STUDENTS - Jogi, Vedavati Ravindra (SCHOOL SCIENCE, 2011)
Many centuries ago Aristotle had observed, ‘What we have to learn, we learn by doing’. However, quite contrary to this observation, in typical Indian Education system, which is mainly examination-centric, learning science in school is by rote, which is the most unscientific way of learning science ! Learning by rote may fetch marks but can neither create scientific temper nor can develop scientific mindset. Breaking away from the conventional path of producing video films for children with professional support, the author has tried to tap the spirit of innovation and creativity in children themselves to produce video clips that have a direct relevance to their studies. The present paper discusses, the objectives, methodology, observations and inferences that could be drawn from personal observations and the products, viz., video clips created by the students which throw light on how video with participatory approach can bring about qualitative change in participating student’s personality as a ‘student of science’.